The History of the Latin Language in The Development of Medical Terminology and The Structure of Modern Word-Formation - Eshbaeva Nargiza Uralovna; Eshbaeva kamila Uralovna (Scientific Trends, 2024)
The article is a study of the structure of a word, its division into root and affixal morphemes, the subject of morphological or morphemic analysis, word formation, and the study of certain word formation models. The problem of word formation analyzed from the study of the vocabulary of modern Romance-Germanic languages, finding a solution to the problem, to the study of their history.
Keywords: Latin alphabet, phonetics, grammar, modern medical nomenclature, word formation issues, classics.